Faktor Determinan Stunting pada Balita : Tinjauan Literatur - Gusriani Gusriani; Nur Indah Noviyanti; Wahida Wahida; Ruqaiyah Ruqaiyah; Mega Octamelia (JURNAL KESEHATAN DELIMA PELAMONIA, 2023)
Stunting is a condition of inhibited or stunted body growth caused by chronic malnutrition that is not addressed properly and promptly. Stunting is one of the nutritional problems that occur worldwide, including in Indonesia. There are many factors that can cause stunting. The purpose of this study is to review the factors that can lead to stunting in toddlers.The study was conducted by conducting a literature review through searching relevant articles from various electronic databases (Google Scholar, DOAJ, Pubmed, portal garuda) using keywords such as "stunting," "toddler," "determinant factors," "stunting incidence," "factors of stunting occurrence," and "stunted toddlers." A total of 11 articles were found with a time limit from 2017 to 2022, and then a thorough analysis was carried out.The results of this study indicate that factors contributing to stunting in toddlers include low maternal education and mothers' inadequate knowledge regarding meeting their children's nutritional needs, lack of exclusive breastfeeding, inappropriate introduction of complementary feeding according to age, a history of infectious diseases such as Acute Respiratory Infections (ARI) and recurrent diarrhea, poor environmental sanitation, and low socioeconomic status in fulfilling children's nutritional needs.Appropriate and effective management is required to address the issue of stunting so that it does not become a factor that hinders children's growth and development in the future. Keywords: stunting, toddlers, determinant factors